2004
DOI: 10.1124/mol.65.3.538
|View full text |Cite
|
Sign up to set email alerts
|

8R-Lisuride Is a Potent Stereospecific Histamine H1-Receptor Partial Agonist

Abstract: The human histamine H 1 receptor (H 1 R) is an important, well characterized target for the development of antagonists to treat allergic conditions. Many neuropsychiatric drugs are known to potently antagonize the H 1 R, thereby producing some of their side effects. In contrast, the tolerability and potential therapeutic utility of H 1 R agonism is currently unclear. We have used a cell-based functional assay to evaluate known therapeutics and reference drugs for H 1 R agonist activity. Our initial functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…The SK-N-MC/hH 3 cell homogenates were incubated for 40 min at 25°C with approximately 1 nM [ 3 H]N ␣ -methylhistamine in 25 mM KPO 4 buffer and 140 mM NaCl (pH 7.4 at 25°C), with or without competing ligands, whereas the SK-N-MC/hH 4 cell homogenates were incubated 1 h at 37°C in 10 nM [ 3 H]histamine and 50 mM Tris-HCl (pH 7.4 at 37°C), with or without competing ligands. Bound radioligands were collected on 0.3% polyethyleneimine-pretreated Whatman GF/C [and washed three times with 3 ml of ice-cold washing buffer (4°C) containing 25 mM Tris-HCl and 140 mM NaCl (pH 7.4 at 4°C) for the hH 3 R and 50 mM Bakker et al (2004). The binding data were analyzed with Prism 4.0 (GraphPad Software Inc., San Diego, CA), and data are presented as mean Ϯ S.E.M.…”
Section: Methodsmentioning
confidence: 99%
“…The SK-N-MC/hH 3 cell homogenates were incubated for 40 min at 25°C with approximately 1 nM [ 3 H]N ␣ -methylhistamine in 25 mM KPO 4 buffer and 140 mM NaCl (pH 7.4 at 25°C), with or without competing ligands, whereas the SK-N-MC/hH 4 cell homogenates were incubated 1 h at 37°C in 10 nM [ 3 H]histamine and 50 mM Tris-HCl (pH 7.4 at 37°C), with or without competing ligands. Bound radioligands were collected on 0.3% polyethyleneimine-pretreated Whatman GF/C [and washed three times with 3 ml of ice-cold washing buffer (4°C) containing 25 mM Tris-HCl and 140 mM NaCl (pH 7.4 at 4°C) for the hH 3 R and 50 mM Bakker et al (2004). The binding data were analyzed with Prism 4.0 (GraphPad Software Inc., San Diego, CA), and data are presented as mean Ϯ S.E.M.…”
Section: Methodsmentioning
confidence: 99%
“…H 3 R isoform-mediated modulation of cAMP mediated gene transcription activity was measured using the luciferase reporter-gene plasmid pTLNC121-3 (2.5 g/10 6 cells) containing 21 cAMP-responsive elements. Luminescence was assayed 48 h after incubation of transfected cells with ligands as described previously (Bakker et al, 2004b 125 I using the Iodogen method (Pierce, Rockford, IL) and subsequently used in ORF74 radioligand binding studies as described previously (Smit et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Although the well characterized 2-(thiazol-2-yl) ethanamine shows only a moderate efficacy of about 26% of that of histamine with a partial agonist behavior, it clearly demonstrated that the tautomeric shift on the imidazole nitrogen atoms is not an essential structural element. Also with other nonimidazole heterocyclic compounds such as the ergot derivative lisuride (partial) agonist properties intrinsic activity from 0.27 to 1.0 (intrinsic activity of histamine = 1.0) could be observed (Bakker et al, 2004b;Pertz et al, 2004). 2-Phenylhistamines were initially developed as H 1 receptor ligands.…”
Section: E H 1 -Selective Ligandsmentioning
confidence: 99%